Training and Assistance in Scientific Writing for Teachers of Smpn Minasa Tene in Pangkep Regency - Muhammad Alwi; Burhan Burhan; Basmi Basmi; Ahmad Ahmad S; Risnashari risnashari (Universitas Hasanuddin, 2020)
The scientific writing training and assistance is intended for the teachers of SMPN 3 Minasa Tene in Pangkep Regency in 2019 and concerns with the central role of teacher academic landscape at the school. Its primary objective is to provide insights into the many fundamentals of developing skills for scientific paper particularly those that make up the process of composing text for classroom action research. While there is a growing consensus among the teachers that it is important to articulate the standards, knowledge and skills for scientific writing to navigate toward career and professional growth, there remains a significant lack of the rudiments of scientific writing among the teachers. To tackle this, training methodology entails a myriad of instructional approaches including lecturing, questions and answers, discussions, brainstorming, demonstrations and practices of writing classroom action research papers. The results are favorable in the areas that call for substantial improvement in scientific writing skills; 1. A set of activities is set and proceeds to the detailed planning stages according to the objectives and targets; 2. The training captures participants’ attention and productive participation, and ultimately garners favorable responses; 3. Approaches to the training have positive influences on the development of expertise and competent performance of scientific writing for classroom action research; 4. The training consists of a group of Natural Sciences, a group of Mathematics and a group of Indonesian Language, with each presenting one systematic scientific paper of classroom research; and 5. It provides training material course for teacher professional development. These commendable results not only suggest that the training is a good path to improving academic writing skills but also tap into the understanding of how and under which specific conditions academic writing performance is effective. This also calls for future effort into teacher assessment training that concerns with teacher competence to design standardized questions and tests for educational assessment out of concern that the potential educational benefits of student assessment be fully realized.